Identification of Portuguese Armillaria Isolates by Classic Mating-Tests and RFLP-PCR Analysis of the ITS1 Region of Ribosomal DNA - Bragança, Helena; Tenreiro, Rogério; Santos, Natércia (Silva Lusitana, 2004)
The diagnosis of Armillaria, a genus including distinct species of highly woody plantpathogenic root-infecting fungi with worldwide distribution, is usually based on morphological characteristics and mating-tests, although the PCR-based restriction fragment length polymorphism (RFLP-PCR), specifically in nuclear rDNA spacers, have also been applied. In the present study, mating-tests and restriction analysis of Internal Transcribed Spacer 1 (ITS1) were used to identify 20 isolates of a Portuguese Armillaria collection. Although the majority of the diploid isolates (80%) could be identified in diploid-haploid pairings, the method is laborious, takes too much time (up to 2 months), and presents a high rate of inconclusive results. The ITS1 region showed to be a reliable molecular marker for A. mellea, in particular when HinfI restriction analysis is applied, since two fragments with 245 bp and 125 bp have been obtained for this most aggressive species whereas 290 bp and 70 bp were produced from isolates of the other European species. As simple molecular techniques are involved and the whole procedure can be performed in one day, A. mellea identification by ITS1 analysis is a clearly accessible and more advantageous tool to plant pathology laboratories, mainly those involved on the control and preservation of forest trees
The following values have no corresponding Zotero field: publisher: scielopt
Keywords: Armillaria mellea; Cork oak; rDNA; RFLP-PCR; Woody plants

Identification of Portuguese Armillaria Isolates by Classic Mating-Tests and RFLP-PCR Analysis of the ITS1 Region of Ribosomal DNA - Bragança, Helena; Tenreiro, Rogério; Santos, Natércia (Silva Lusitana, 2004)
The diagnosis of Armillaria, a genus including distinct species of highly woody plantpathogenic root-infecting fungi with worldwide distribution, is usually based on morphological characteristics and mating-tests, although the PCR-based restriction fragment length polymorphism (RFLP-PCR), specifically in nuclear rDNA spacers, have also been applied. In the present study, mating-tests and restriction analysis of Internal Transcribed Spacer 1 (ITS1) were used to identify 20 isolates of a Portuguese Armillaria collection. Although the majority of the diploid isolates (80%) could be identified in diploid-haploid pairings, the method is laborious, takes too much time (up to 2 months), and presents a high rate of inconclusive results. The ITS1 region showed to be a reliable molecular marker for A. mellea, in particular when HinfI restriction analysis is applied, since two fragments with 245 bp and 125 bp have been obtained for this most aggressive species whereas 290 bp and 70 bp were produced from isolates of the other European species. As simple molecular techniques are involved and the whole procedure can be performed in one day, A. mellea identification by ITS1 analysis is a clearly accessible and more advantageous tool to plant pathology laboratories, mainly those involved on the control and preservation of forest trees
Keywords: Armillaria mellea; Cork oak; rDNA; RFLP-PCR; Woody plants

Micoflora asociada al alcornoque - MuÑoz LÓPEZ, C; COBOS SUÁREZ, P; MARTÍNEZ SAAVEDRA, G; SOLDEVILLA PUGA, C; DÍAZ LLORENTE, M (II Congreso Forestal Español, 1997)
This proyect intends both to reflect a synthesis of the results obtained in the study of the fungi related to Q. suber L., first in the Parque Natural de los Alcornocales (Cádiz), and then in other areas of Spain, and to highlight the rol of especific fungi detected in the group of all mycetes which are described in the same work
Keywords: Armillaria mellea; diplodia mutila; Hypoxylon mediterraneum; mycology flora; phytophthora cinnamomi; Quercus suber

GC−MS Study of Volatiles of Normal and Microbiologically Attacked Cork from Quercus suber L. - Rocha, Sílvia; Delgadillo, Ivonne; Ferrer Correia, A J (Journal of Agricultural and Food Chemistry, 1996)
The volatile compounds of cork were studied by gas chromatography and combined gas chromatography?high-resolution mass spectrometry using simultaneous distillation?extraction to prepare the samples. To assess the origin of the volatiles, three different types of samples were analyzed:? ?normal?, attacked by Armillaria mellea, and infested by molds. The study of the volatiles of these different types of corks allowed the identification of the chemical modifications which may occur in cork polymers. The cork attacked by A. mellea showed higher amounts of phenols, vanillin, benzaldehyde, benzyl alcohol, and chlorinated compounds than normal cork; this may indicate lignin degradation. The cork infested by molds contained higher levels of 3-methyl-1-butanol, 1-octen-3-ol, 1-octanol, 2-methylisoborneol, chlorinated compounds, and methyl ketones. These components resulting from microbial metabolism were also present in cork attacked by A. mellea. The use of cork attacked by A. mellea is not recommended in the manufacture of cork stoppers, since these types of cork have volatile compounds likely to cause off-flavors in wine. For the same reason it is important to reduce the likelihood of mold development during the standing period. Keywords: ?Normal? cork; Armillaria mellea; molds; volatile components; musty and moldy odors
doi: 10.1021/jf9500400
Keywords: Armillaria mellea; molds; musty and moldy odors; volatile components; “Normal” cork

GC−MS Study of Volatiles of Normal and Microbiologically Attacked Cork from Quercus suber L. - Rocha, Sílvia; Delgadillo, Ivonne; Ferrer Correia, A. J. (Journal of Agricultural and Food Chemistry, 1996)
The volatile compounds of cork were studied by gas chromatography and combined gas chromatography?high-resolution mass spectrometry using simultaneous distillation?extraction to prepare the samples. To assess the origin of the volatiles, three different types of samples were analyzed:? ?normal?, attacked by Armillaria mellea, and infested by molds. The study of the volatiles of these different types of corks allowed the identification of the chemical modifications which may occur in cork polymers. The cork attacked by A. mellea showed higher amounts of phenols, vanillin, benzaldehyde, benzyl alcohol, and chlorinated compounds than normal cork; this may indicate lignin degradation. The cork infested by molds contained higher levels of 3-methyl-1-butanol, 1-octen-3-ol, 1-octanol, 2-methylisoborneol, chlorinated compounds, and methyl ketones. These components resulting from microbial metabolism were also present in cork attacked by A. mellea. The use of cork attacked by A. mellea is not recommended in the manufacture of cork stoppers, since these types of cork have volatile compounds likely to cause off-flavors in wine. For the same reason it is important to reduce the likelihood of mold development during the standing period. Keywords: ?Normal? cork; Armillaria mellea; molds; volatile components; musty and moldy odors
doi: 10.1021/jf9500400doi: 10.1021/jf9500400The following values have no corresponding Zotero field: publisher: American Chemical Society
Keywords: Armillaria mellea; molds; musty and moldy odors; volatile components; “Normal” cork